Performance of non‐conventional yeasts in co‐culture with brewers’ yeast for steering ethanol and aroma production - van Rijswijck, Irma M. H. (Microb Biotechnol, 2017)
Increasing interest in new beer types has stimulated the search for approaches to extend the metabolic variation of brewers’ yeast. Therefore, we tested two approaches using non‐conventional yeast to create a beer with lower ethanol content and a complex aroma bouquet. First, the mono‐culture performance was monitored of 49 wild yeast isolates of Saccharomyces cerevisiae (16 strains), Cyberlindnera fabianii (9 strains) and Pichia kudriavzevii (24 strains). Interestingly, both C. fabianii and P. kudriavzevii isolates produced relatively more esters compared with S. cerevisiae isolates, despite their limited fermentation capacity. Next, one representative strain of each species (Sc131, Cf65 and Pk129) was applied as co‐culture with brewers’ yeast (ratio 1:1). Co‐cultures with Cf65 and Pk129 resulted in a beer with lower alcohol content (3.5, 3.8 compared with 4.2% v/v) and relatively more esters. At higher inoculum ratios of Cf65 over brewers’ yeast, growth inhibition of brewers’ yeast was observed, most likely caused by competition for oxygen between brewers’ yeast and Cf65 resulting in a reduced level of ethanol and altered aroma profiles. With this study, we demonstrate the feasibility of using non‐conventional yeast species in co‐cultivation with traditional brewers’ yeast to tailor aroma profiles as well as the final ethanol content of beer.